Рассказы - Чехов Антон Павлович (Классика - детям, 2001)
Экземпляры: Селтинская детская библиотека (20240328) / Инвентарный номер: 184434 / Цена: / Авт.знак: Ч-56 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)1